Agricultural value chain finance in Indonesia - de Brauw, Alan; Herskowitz, Sylvan; Ambler, Kate; Sayaka, Bambang; Pasaribu, Sahat M.; Dabukke, Frans B. M.; Suhartini, Sri Hastuti; Suryani, Erma; Suwarno, Agus; Moyes, Tom (International Food Policy Research Institute, 2021)
Smallholder farmers in developing countries face substantial constraints that limit their ability to reach their production potential. Two constraints—risk exposure and limited access to liquidity—pose particular challenges. Smallholders face a wide variety of risks that constrain both the choices they can make and their willingness to make investments. Limited availability of affordable credit, borrowing and saving products poorly aligned with the needs of the agriculture sector, and prohibitive borrowing eligibility requirements all impede farmers’ access to the liquidity necessary for investing in new, more profitable crops and technologies (International Finance Corporation, 2014). Observers have noted that a large share of long-term credit needs is not being met in Southeast Asia, despite its location near some of the world’s largest consumer markets (Shakhovskoy & Wendle, 2013). While existing financial services may be suitable for some farmers, access to finance is particularly inadequate among women, low-income groups, and ethnic minorities, and risk excluding the most vulnerable groups from these emerging economic opportunities.